Skilled-labour crisis in Thailand: prognosis, policies and prospects - Min Ye Paing Hein (2024)
Thailand is experiencing an acute shortage of skilled labour. First, its working-age population has been shrinking. Secondly, the supply of skilled labour has been declining. Thirdly, a large proportion of youths and adults lack digital skills. In response, the Thai government has been experimenting with myriad policy instruments but would benefit from a whole-of-government strategy.